Out-of-Field Teaching: Impact on Teachers’ Self-Efficacy and Motivation - Recede, Reynald Alfred A.; Asignado, Rowena A.; Castro, Mark A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
he study aimed to determine the impact of having teaching loads assigned to teachers which are not aligned with their preservice training. The research utilized a descriptive research design and involved 12 senior high school teachers who are teaching in a public national high school in Marikina City, the Philippines for the school year 2019-2020. The study also made use of the qualitative data gathered through focus group discussion to have an in-depth analysis of the perceptions of the teachers regarding their situation on teaching a subject that is not part of their expertise. The study revealed that teachers who are assigned teaching loads which are not part of their preservice training showed some confidence that they can teach their students well. This was shown on the question how confident they were in teaching their students to become critical thinkers and 8 or (66.67 %) of the total number of the teacher participants said that they exerted moderate effort in encouraging students to become critical thinkers. In addition, 5 or (41.67 %) of the teachers shared that they can do so much to help students improve in his failing grade. Surprisingly, 7 or (58.33%) of the total number of the teacher participants said that they can only exert moderate effort to help students who are having difficulty with the subject. Based from the findings of the study, the researchers thought that the perennial problem of teachers being assigned teaching loads that are not in line with their area of expertise should be given enough training and technical assistance coming from the school administration. This will help improve teachers in their pedagogical techniques and the type of assessment they employ in their classes.